CORRELATION BETWEEN STUDENTS’ INTEREST IN WATCHING YOUTUBE AND THEIR LISTENING ABILITY - Arya Bagus Malik Fajar; Iman Santoso (IKIP Siliwangi, 2024)
YouTube as an instructive device has been as of late getting a lot of consideration from scientists and educators. The concentrate being referred to consequently researches this peculiarity. The motivation behind this exploration is to figure out understudies' advantage in watching YouTube. The information assortment procedure utilized in this exploration is a quantitative technique. The complete populace taking the test is class VII of SMK PGRI 1 Cianjur. This data was collected through surveys and tests, then the data was collected using a relationship test. Considering the outcome of assessment data, there was a connection between's students interest in watching Youtube video and their capacity to tune in. The specialists Reason that understudies' advantage in watching Youtube recordings influences their listening skill in view of the discoveries and understanding gave previously. The researchers recommended using an English song's music video as a teaching tool because the research showed that interest plays a crucial role in students' learning processes, particularly in developing their listening skills. Due to the students' interest in the music video, it might advance and lay out a charming educational experience. Subsequently, the understudies will take part effectively in class and not get exhausted in light of the fact that they are excited about the topic.